Exposição ocupacional de fisioterapeutas aos campos elétrico e magnético e a eficácia das gaiolas de Faraday - De Anchieta Messias, Iracimara [UNESP]; Okuno, Emico; Colacioppo, Sérgio (My University, 2011)
Objective. Measure physical therapists' exposure to the electric and magnetic fields produced by 17 shortwave diathermy devices in physical therapy clinics in the city of Presidente Prudente, São Paulo State, Brazil. Compare the observed values with the exposure levels recommended by the International Commission on Non-ionizing Radiation Protection (ICNIRP). Observe the efficacy of Faraday cages as a means of protecting physical therapists from exposure to oscillating electric and magnetic fields. Methods. Electric and magnetic field measurements were taken at four points during actual physical therapy sessions: in proximity to the operator's pelvis and head, the devices' electrical cables, and the electrodes. The measuring equipment was a Wandel & Goltermann EMR-200. Results. The values obtained in proximity to the electrodes and cables were 10 to 30 times higher than ICNIRP's recommended occupational reference levels. In the shortwave diathermy treatment rooms with Faraday cages, the fields were even higher than in treatment rooms not so equipped-principally the magnetic field, where the values were more than 100 times higher than the ICNIRP exposure limit. Conclusions. The electric and magnetic field intensities obtained in this study are generally above the exposure levels recommend in ICNIRP standards. It was also observed that the Faraday cage offers physical therapists no protection, and instead, increases their level of exposure.
Occupational exposure of physical therapists to electric and magnetic fields and the efficacy of Faraday cages
Keywords: Brazil; Diathermy; Electromagnetic fields; Nonionizing; Occupational exposure; Physical therapy; Radiation; Short-wave therapy